Electronic slide matching and enhancement of a lecture video - KOKARAM, ANIL CHRISTOPHER; PITIE, FRANCOIS (My University, 2007)
This paper presents an automatic method to enhance video presentations for distance learning applications. From a material recorded by a fixed, non professional camera, the system matches the slides displayed during the presentation with their electronic versions. The process to achieve slide recognition consists of two phases. In the first phase, the location where the slides are displayed is located by colour matching. Then a shot detection is performed in the display area and a frame is selected for each slide displayed in the video. The second phase consists of matching the frames previously selected to the electronic version of the slides. Using correlation measure, a likelihood is computed for each electronic slide to correspond to the slides displayed in the frames selected. A prior distribution is then defined to model the probability of each possible slide transition. Finally the most probable sequence of slides displayed in the video is determined using the Viterbi algorithm. The results show that the method presented is robust against luminance conditions, occlusion by the lecturer and can be performed for a large variety of presentations.
Visual Media Production
IETCVMP. 4th European Conference on Visual Media Production, 2007.
PUBLISHED
London
Keywords: Electronic & Electrical Engineering